2017
DOI: 10.1002/lary.26599
|View full text |Cite
|
Sign up to set email alerts
|

Investigating hyperventilation syndrome in patients suffering from empty nose syndrome

Abstract: 2b Laryngoscope, 127:1983-1988, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 31 publications
(70 reference statements)
0
52
0
Order By: Relevance
“…The difference in the shape and slope of the pressure profile could also suggest that deeper, more forced breaths (which would increase the pressure drop) may be needed to mimic normal, healthy breathing. Mangin et al showed that one potential effect of continual deep breathing is hyperventilation as well as hypocapnia, which is one of the symptoms cited by longstanding, chronic ENS patients. With the insertion of cotton, it is possible that the need to compensate for these pressure discrepancies through deep breathing may no longer be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the shape and slope of the pressure profile could also suggest that deeper, more forced breaths (which would increase the pressure drop) may be needed to mimic normal, healthy breathing. Mangin et al showed that one potential effect of continual deep breathing is hyperventilation as well as hypocapnia, which is one of the symptoms cited by longstanding, chronic ENS patients. With the insertion of cotton, it is possible that the need to compensate for these pressure discrepancies through deep breathing may no longer be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ENS may also experience mucosal dryness, nasal congestion, facial pain and headache on inspiration, and excessive nasal crusting and discharge (1,2,7) . Affected patients often report a significant negative impact on the quality of life (QOL) and psychological status, productivity loss, and lifestyle disruption (8)(9)(10) . As a result, a validated instrument, the Sinonasal Outcome Test-25 (SNOT-25), was developed by Houser (2) .…”
Section: Introductionmentioning
confidence: 99%
“…These five additional items may better assess the symptoms of ENS patients (7) . ENS patients also experience anxiety and depression that may lead to suicide attempts in extreme cases (8)(9)(10) . Our previous study (10) using validated instruments including the Beck Depression Inventory-II (BDI-II) (11) and Beck Anxiety Inventory (BAI) (12) found that depression and anxiety are common among ENS patients and could be effectively improved after surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a recent article that addresses hyperventilation syndrome in patients suffering from empty nose syndrome was published in 2017. 284 However, nasal breathing after turbinate and septal surgery can cause seemingly unexplained complications with a MAD. It is recommended to include a question in the health intake questionnaire asking if this surgery has been performed by those providing MAD therapy for OSA patients.…”
Section: Sleep-related Breathing Disordersmentioning
confidence: 99%